1 Answer | Add Yours
I'm not sure if `ab!` means multiply `a` and `b` and then compute the factorial of the product, as in `(ab)!,` ` ` or first compute the factorial of `b` and then multiply this by `a,` as in ` ` `a(b!),` but either way the statement is false. Just try some small numbers to get a counterexample. Let `a=2,b=3.` Then
`(ab)! =(2*3)! =6! =720,` while `a(b!)=2*(3!)=2*6=12.`
Since neither of the last two equals 6, the statement is false.
We’ve answered 319,865 questions. We can answer yours, too.Ask a question